EXPLORING THE POSSIBILITIES OF USING A DEVELOPED REMOTELY CONTROLLED MOBILE ROBOT - Šaulys, Povilas; Niauronis, Saulius; Dargužis, Andrius (PROFESSIONAL STUDIES: Theory And Practice, 2023)
This article examines the construction of a remotely controlled mobile robot created 5 years ago at Alytus College, the possibilities of its use and the study of the possibilities of its use. During the study, the created mobile robot with other robots developed by foreign scientists is analyzed and compared and a corresponding way to use it is sought.